Risk Factors of Redo Surgery After Unilateral Focused Parathyroidectomy: Conclusions From a Comprehensive Nationwide Database of 13, 247 Interventions Over 6 Years. Issue 5 (November 2020) - Donatini, Gianluca; Marciniak, Camille; Lenne, Xavier; Clément, Guillaume; Bruandet, Amélie; Sebag, Frédéric; Mirallié, Eric; Mathonnet, Muriel; Brunaud, Laurent; Lifante, Jean-Christophe; Tresallet, Christophe; Ménégaux, Fabrice; et al.
Abstract : Background: Surgical removal of hyperfunctional parathyroid gland is the definitive treatment for primary hyperparathyroidism (pHPT). Postoperative follow-up shows variability in persistent/recurrent disease rate throughout different centers. Objective: To evaluate the incidence of redo surgery after targeted parathyroidectomy for pHPT. Methods: We performed a nationwide retrospective cohort study on the "Programme de Medicalisation des Systemes d'Information, " the French administrative database that collects information on all healthcare facilities' discharges. We extracted data from 2009 to 2018 for all patients who underwent parathyroidectomy for pHPT between January 2011 to December 2016. The primary outcome was the reoperation rate within 2 years since first surgery. Patients who had a first attempt of surgery within the previous 24 months, familial hyperparathyroidism, multiglandular disease, and renal failure were excluded. Results were adjusted according to sex and the Elixhauser Comorbidity Index. Operative volume thresholds to define high-volume centers were achieved by the Chi-Squared Automatic Interaction Detector method. Results: In the study period, 13, 247 patients (median age 63, F/M=3.6) had a focused parathyroidectomy by open (88.7%) or endoscopic approach. Need of remedial surgery was 2.8% at 2 years. In multivariate analysis, factors predicting redo surgery were: cardiac history ( P =0.008), obesity ( P =0.048), endoscopic approach ( P =0.005), and low-volume center ( P <0.001). We evaluated that an annual caseload of 31 parathyroidectomies was the best threshold to discriminate high-volume centers and carries the lowest morbidity/failure rate. Conclusion: Although focused parathyroidectomy represents a standardized operation, cure rate is strongly associated with annual hospital caseload, type of procedure (endoscopic), and patients' features (obesity, cardiac history). Patients with risk factors for redo surgery should be considered for an open surgery in a high-volume center. Abstract : Supplemental Digital Content is available in the text